2019
DOI: 10.1177/0486613419849683
|View full text |Cite
|
Sign up to set email alerts
|

Semi-private Landownership and Capitalist Agriculture in Contemporary China

Abstract: Although the existing scholarship on the capitalist transformation of Chinese agriculture uses the concepts of the Marxist political economy to analyze class differentiation, it has not systematically analyzed the role of the Chinese state (as manifested in the current semi-private land system) in this transformation with reference to Marx’s theory of agricultural rent. Capitalist transformation of Chinese agriculture in the context of continuing strong government control over farmland provides a unique opport… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 37 publications
1
7
0
Order By: Relevance
“…This does not mean that the village collective has greater power than local authorities in negotiation. The experience of Mengke village is the same as what Gürel (2019) observes:
Local government acts as the main agent in land deals, including the acquisition of rural land, without having to deal with each and every property owner in order to convince them to give up their land for a development project.
…”
Section: The Shareholding Cooperative Companymentioning
confidence: 85%
See 3 more Smart Citations
“…This does not mean that the village collective has greater power than local authorities in negotiation. The experience of Mengke village is the same as what Gürel (2019) observes:
Local government acts as the main agent in land deals, including the acquisition of rural land, without having to deal with each and every property owner in order to convince them to give up their land for a development project.
…”
Section: The Shareholding Cooperative Companymentioning
confidence: 85%
“…However, this does not mean the village collective holds absolute control over the land deals. In reality, Gürel (2019) found that, even though shareholding companies that own land are not SOEs (stated‐owned enterprises) by law, government officials are heavily involved in their foundation and daily management in some villages. This is because the critical feature of the Chinese land system is that “local government bodies above the village level in terms of hierarchy usually have greater power than the village collective in every aspect of land deals” (Gürel 2019: 659).…”
Section: Institutional Transformations Village Corporatism and Shareholding Companies In Chinamentioning
confidence: 99%
See 2 more Smart Citations
“…With the rapid development of urban land marketization and town and village enterprises (TVEs), the land, especially urban land became more and more scarce [3,4]. In order to meet demand of urban economic development and TVEs, the local government legally or illegally converted farmland at the rural-urban fringe or superior location to absorb the investment of foreign capital, China's Hong Kong, China's Taiwan, or joint venture [5][6][7]. The strategy of substitution of capital for land on one hand booms China's eastern coastal area, on the other hand gives rise to huge stock construction lands in rural and urban areas [8].…”
Section: Introductionmentioning
confidence: 99%